10-year Characteristics of Moisture Source Regions and Their Potential Effect on Seasonal Isotopic Signatures of delta O-18 in Tropical Trees of Southern Ecuador - Landshuter, Nadja; Mölg, Thomas; Grießinger, Jussi; Bräuning, Achim; Peters, Thorsten (Frontiers in Earth Science, 2020)
Ratios of stable oxygen isotopes in tree rings (delta O-18) are a valuable proxy for reconstructing past climates. Such reconstructions allow us to gain better knowledge of climate dynamics under different (eg warmer) environmental conditions, which also forms the basis for effective risk management. The latter aspect is particularly relevant for our study site on the western flanks of the Andes in Southern Ecuador, since the region is frequently affected by droughts and heavy precipitation events during the rainy season (January to April), leading to enormous social and economic losses. In particular, we focus on precipitation amounts and moisture source regions as they are known to influence the delta O-18 signature of tree rings. Moisture source regions are based on 240 h backward trajectories that were calculated with the trajectory model LAGRANTO for the rainy seasons 2008 to 2017. A moisture source diagnostic was applied to the air parcel pathways. The resulting moisture source regions were analyzed by calculating composites based on precipitation amounts, season, and calendar year. The precipitation amounts were derived from data of a local Automatic Weather Station (AWS). The analysis confirms that our study site receives its moisture both, from the Atlantic and the Pacific Oceans. Heavy precipitation events are linked to higher moisture contributions from the Pacific, and local SST anomalies along the coast of Ecuador are of higher importance than those off the coast toward the central Pacific. Moreover, we identified increasing moisture contributions from the Pacific over the course of the rainy season. This change and also rain amount effects are detectable in preliminary data of delta O-18 variations in tree rings of Bursera graveolens. These signatures can be a starting point for investigating atmospheric and hydroclimatic processes, which trigger delta O-18 variations in tree rings, more extensively in future studies.
CRIS-Team WoS Importer:2021-02-26

Stable Water Isotope Signals and Their Relation to Stratiform and Convective Precipitation in the Tropical Andes - Landshuter, Nadja; Aemisegger, Franziska; Mölg, Thomas (Journal of Geophysical Research: Atmospheres, 2024)
Stratiform and convective precipitation are known to be associated with distinct isotopic fingerprints in the tropics. Such rain type specific isotope signals are of key importance for climate reconstructions derived from climate proxies (e.g., stable isotopes in tree rings). Recently, the relation between rain type and isotope signal in present-day climate has been intensively discussed. While some studies point out the importance of deep convection, other studies emphasize the role of stratiform precipitation for strongly depleted isotope signals in precipitation. Uncertainties arise from observational studies due to data scarcity while modeling approaches with global climate models cannot explicitly resolve convective processes and rely on parameterizations. High-resolution climate models are particularly important for studies over complex topography and for the simulation of convective cloud formation and organization. Therefore, we applied the isotope-enabled version of the high-resolution climate model from the Consortium for Small-Scale Modeling (COSMOiso) over the Andes of tropical south Ecuador, South America, to investigate the influence of stratiform and convective rain on the stable oxygen isotope signal of precipitation (δ18OP). Our results highlight the importance of deep convection for depleting the isotopic signal of precipitation and increasing its deuterium excess. Due to the opposing effect of shallow and deep convection on the δ18OP signal, the use of a stratiform fraction might be misleading. We therefore propose to use a shallow and deep convective fraction to analyze the effect of rain types on δ18OP.
CRIS-Team Scopus Importer:2024-08-02
Keywords: convection; Ecuador; high-resolution; isotope-enabled climate modeling; rain types; stable water isotopes; tropical South America